1988
DOI: 10.1111/j.1365-4362.1988.tb02404.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Mast Cell Quantity in Pruritic and Nonpruritic Hemodialysis Patients

Abstract: Pruritus remains a significant complication of end-stage renal disease. Its cause in hemodialysis patients is not known. It has been postulated that increased numbers of mast cells occur in these patients and may account for the presence of pruritus. Our objective was to determine if there is a difference in the number of cutaneous mast cells between pruritic and nonpruritic patients. A 3-mm punch biopsy specimen was obtained from pruritic (n = 7) and nonpruritic (n = 6) hemodialysis patients. We observed no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
2
7
0
1
Order By: Relevance
“…9 The mechanisms of UP are still unclear; however, many molecules that are abnormally accumulated in patients with ESRD have been implicated in the pathogenesis of itching. 12,13 This is consistent with our observation that haemodialysis has the ability to relieve UP through the clearance of accumulated substances. Histamine is a well-known pruritogen and can directly stimulate the neurone terminals by H1 receptors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…9 The mechanisms of UP are still unclear; however, many molecules that are abnormally accumulated in patients with ESRD have been implicated in the pathogenesis of itching. 12,13 This is consistent with our observation that haemodialysis has the ability to relieve UP through the clearance of accumulated substances. Histamine is a well-known pruritogen and can directly stimulate the neurone terminals by H1 receptors.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to histamine, high serum levels of small molecule substances such as Ca 2+ , PO 4 3) , Mg 2+ , raised skin content of divalent ions, and hypervitaminosis A have been also inconclusively considered as linked to the presence of pruritus in patients with ESRD. 12,13 This is consistent with our observation that haemodialysis has the ability to relieve UP through the clearance of accumulated substances.…”
Section: Discussionsupporting
confidence: 91%
“…An anatomic abnormality in the pattern of the enolase‐positive fibers was reported to be present in pruritic ESRD patients, 28 but this has not been further substantiated 29 . Numbers of skin mast cells and serum levels of histamine are increased in uremic patients but this seems to occur irrespective of the presence of pruritus 27,30 . Additional factors have been inconclusively implicated with the presence of pruritus in ESRD patients including high serum levels of Ca, P, Mg, PTH, aluminum, and substance P; elevated cutaneous content of divalent ions; hypervitaminosis A; and peripheral neuropathy 25,27 , 31,32 .…”
Section: Pathogenesismentioning
confidence: 99%
“…29 Numbers of skin mast cells and serum levels of histamine are increased in uremic patients but this seems to occur irrespective of the presence of pruritus. 27,30 Additional factors have been inconclusively implicated with the presence of pruritus in ESRD patients including high serum levels of Ca, P, Mg, PTH, aluminum, and substance P; elevated cutaneous content of divalent ions; hypervitaminosis A; and peripheral neuropathy. 25,27,31,32 More recently, a substantial body of evidence has been accumulated in favor of the concept that the uremic state is a chronic inflammatory condition in which a number of proinflammatory cytokines are activated.…”
Section: Pathogenesismentioning
confidence: 99%
“…A role for hista mine has recently been relaunched by Stockenhuber et al [36] , who found increased plasma histamine levels in HD patients with pruritus compared to those without pruritus. Others, however, could not find any difference in plasma histamine levels between pruritic and nonpruritic patients [24], as well as between patients on HD or CAPD [37], It would be possible that uremic pruritus is caused by an abnormal histamine reactivity. Stahle-Backdahl [28] showed that the itch responses in uremic patients with pruritus were significantly greater than in nonpruritic urem ics or controls, indicating an increased sensitivity to pruritogenic stimuli.…”
Section: Pathophysiology Of Uremic Pruritusmentioning
confidence: 99%